The Audit Staff Assignment Problem: A Linear Programming Analysis. - Summers, Edward L. (The Accounting Review, 1972)
This paper discusses the assignment of audit staff personnel to audit engagements to conform to the limitations of an audit office and at the same time meet the unique professional and economic objectives of that office. A linear programming model of this assignment problem is being discusses which not only provides an assignment that maximizes a linear function describing the audit office's professional and economic objectives, but provides other useful information for decisions such as scheduling of professional development and education, etc. The proposed model has a significant potential limitation–the benefit–maximizing nature of linear programming. Auditors do not seek to maximize profits or billings but rather to serve the public as well as possible and earn a satisfactory compensation. Hence, the model cannot simply maximize office billings. The steps which have been taken to construct a useful measure of audit office benefits for maximization overcomes this limitation, and will be described in the paper.